MINIREVIEW: KEPENTINGAN TRICHODERMA DALAM SISTIM PERTANIAN BERKELANJUTAN - Agus Purwanto (Program Studi Biologi - Universitas Katolik Widya Mandala Surabaya (kampus Kota Madiun), 2022)
ABSTRACT The results of reference studies in journals related to the potential of Trichoderma spp fungi in the application of sustainable agroecosystems can be reported that the best solution to overcome food safety and environmental problems is the application of biological control using Trichoderma spp. Its antagonistic properties with plant pathogenic microorganisms make it more reliable for use in agriculture. Several research results reported that Trichoderma spp is known to have the ability to attack other fungi so that it has the potential as a potential biological control agent. Secondary metabolites secreted by Trichoderma spp. has proven its role in suppressing the growth of pathogenic microorganisms and stimulating plant growth. Several research results reported that Trichoderma spp. as natural decomposition agent and bioremediation biological agent Key word: Trichoderma spp, sustainable agroecosystem, application